2018
DOI: 10.3390/ma11010063
|View full text |Cite
|
Sign up to set email alerts
|

The Study on the Overall Plasma Electrolytic Oxidation for 6061–7075 Dissimilar Aluminum Alloy Welded Parts Based on the Dielectric Breakdown Theory

Abstract: Electrical connection of dissimilar metals will lead to galvanic corrosion. Therefore, overall surface treatment is necessary for the protection of dissimilar metal welded parts. However, serious unbalanced reactions may occur during overall surface treatment, which makes it difficult to prepare integral coating. In this paper, an overall ceramic coating was fabricated by plasma electrolytic oxidation to wrap the 6061–7075 welded part integrally. Moreover, the growth mechanism of the coating on different areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
(36 reference statements)
0
3
0
4
Order By: Relevance
“…Jiang et al formed thick epoxy coatings (~100 ± 10 μm) on AA2024 aluminium alloy [2,3]. Among the methods of protective coating formation on the surface of Al alloys, one of the most promising methods is plasma electrolytic oxidation [5,6,7,8,9,10,11,12,13,14,15]. Serdechnova et al grew layered double hydroxides on PEO-pretreated AA2024 Al alloy [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jiang et al formed thick epoxy coatings (~100 ± 10 μm) on AA2024 aluminium alloy [2,3]. Among the methods of protective coating formation on the surface of Al alloys, one of the most promising methods is plasma electrolytic oxidation [5,6,7,8,9,10,11,12,13,14,15]. Serdechnova et al grew layered double hydroxides on PEO-pretreated AA2024 Al alloy [6].…”
Section: Introductionmentioning
confidence: 99%
“…Egorkin et al formed protective coatings on 5754 Al alloy with high mechanical and protective properties using PEO in a mixed electrolyte with microsecond polarizing current pulses [14]. Chen et al showed that PEO can effectively inhibit dissimilar aluminium alloy welded parts against galvanic corrosion [15]. The properties of the formed surface layers depend on the polarization mode of PEO, electrolyte composition, and chemical composition and structure of the treated alloy [16,17,18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…They noted that PEO coating has improved hardness and corrosion resistance. Chen et al [58] used PEO as a process tool to protect the weldment involving dissimilar materials combination of 6061 and 7075 Al alloys. They noted that the PEO oxide coverage on the weldment has different morphology and composition compared to PEO coating on the substrate materials.…”
Section: Peo Of 6061 Al Alloysmentioning
confidence: 99%
“…Например, формируются толстые эпоксидные покрытия (~100 ± 10 мкм) на алюминиевом сплаве AA2024 [824,825]. Для создания защитных покрытий на алюминиевых сплавах активно используется плазменное электролитическое оксидирование [49,81,86,88,145,543,544,552,[827][828][829][830][831][832]. Получены ПЭО-слои на алюминиевых композитах в силикатно-щелочном электролите при переменнотоковом режиме оксидирования [831].…”
Section: антикоррозионные покрытия для алюминиевых сплавов и их сварн...unclassified
“…На поверхности алюминиевого сплава 5754 методом ПЭО были созданы защитные покрытия с высокими механическими и защитными свойствами в электролите смешанного состава с использованием поляризующих импульсов тока микросекундной длительности [552]. Показано, что методом ПЭО можно эффективно снижать гальваническую коррозию на поверхности сварных деталей из различных алюминиевых сплавов [827]. Исследованы зависимости свойств сформированных покрытий от режима ПЭО, состава электролита, состава и структуры обрабатываемого алюминиевого сплава [284,[833][834][835][836][837].…”
Section: антикоррозионные покрытия для алюминиевых сплавов и их сварн...unclassified